Infant atopic eczema and subsequent attention-deficit/hyperactivity disorder - A prospective birth cohort study - Genuneit, J.; Braig, S.; Brandt, S.; Wabitsch, M.; Florath, Ines; Brenner, H.; Rothenbacher, D. (2014)
Background: Comorbidity between childhood atopic eczema (AE) and attention-deficit/hyperactivity disorder (ADHD) has been observed, but temporal relationships remain unclear. Methods: We analyzed data of a population-based, prospective birth cohort study among 770 children included at baseline in 2000/2001 with follow-up up to age 11. Information on age at diagnosis of AE, rhinoconjunctivitis, and ADHD was obtained by questionnaires administered to parents and for AE also to caring physicians. Adjusted relative risks (aRR) with 95% confidence intervals (95% CI) were modeled with a modified Poisson regression. Results: Early AE up to age 4 yr was reported for 14.8% of the children by the parents and for 26.0% by the physicians with only fair agreement between these reports (kappa = 0.36). Based on parental reports, the association of early AE with early ADHD was strong (aRR: 5.17, 95% CI: 2.18; 12.28), but absent for late ADHD [aRR: 0.50 (0.13; 2.02)]. The association of late AE with late ADHD [aRR: 3.03 (0.75; 12.29)] was not statistically significant. This pattern was independent of the presence of rhinoconjunctivitis. Conclusions: The observed comorbidity between AE and ADHD may indicate vulnerability to develop ADHD symptoms in response to AE symptoms or through a common underlying mechanism. This vulnerability seems to decrease with time since AE onset and may be greater in early life. These temporal relationships should be considered in future research investigating mechanisms linking both diseases and in clinical efforts to screen for and prevent ADHD symptoms in children with AE. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.